A benefit-cost analysis of establishing a regional conservation area in San Ignacio, Cajamarca - Arellanos Carrión, Erick Stevinsonn (2020)
The Regional Government of Cajamarca started in 2014 the recognition process as a regional conservation area of ​​the El Chaupe, Cunia and Chinchiquilla Forests. The objective of this study was to estimate the social benefits and costs for the establishment of the conservation area, which will serve the regional authority to manage its creation. In order to achieve the objective, a contingent valuation study was carried out in order to estimate the economic value of the main services provided by forests, after which, these values ​​were added to infer the social benefits they generate in a scenario of improvements through conservation programs. In addition, the probable costs of the optimal management of the area in which installation and program costs with long-term vision are included were estimated. The investigation concludes that the net social benefits range between 25 and 29 million soles annually, and profitability indicators show that public investment is justified for the establishment of the regional conservation area.